Can domestic institutions affect exports and innovation? Mediation effects of institutional quality on manufacturing sector exports and innovation in developing countries - Achinthya Koswatta (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Studies show that when exports go up, innovation goes up as well. But what is the mediating effect of domestic institutions in the association between exports and innovation? If any, which institutions are more likely to improve exports and innovation in developing countries, and how? To address this lacuna, this study employs estimations of industry fixed effects for 22 two-digit manufacturing industries in the period from 1996 to 2018. The first estimation includes 57 developing countries, and the second estimation excludes extreme outliers or unusual countries from the sample. The study finds that poor-quality institutions cause negative effects in the relationship between manufacturing sector exports and innovation in developing countries. Among the five institutional quality groups considered, the strongest negative effects can be observed for legal institutions (legal environment) in developing countries.
Keywords: F14; E02; O32; 330; innovation; mediating effect; domestic institutions; industry fixed effects; manufacturing industries; poor-quality institutions; legal institutions